2016
DOI: 10.1016/s2214-109x(16)30183-8
|View full text |Cite
|
Sign up to set email alerts
|

Asking different questions: research priorities to improve the quality of care for every woman, every child

Abstract: Asking diff erent questions: research priorities to improve the quality of care for every woman, every child Unacceptably high rates of adverse outcomes persist for childbearing women and infants, including maternal and newborn mortality, stillbirth, and short-term and long-term morbidity. 1 In light of the challenges to achieve the UN Sustainable Development Goals, it is timely to reconsider priorities for research in maternal and newborn health. Are we asking the right questions? 2 Recent evidence indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 12 publications
1
61
0
Order By: Relevance
“…Information about maternity care providers’ perspectives regarding prenatal preparation for physiologic birth, similar to women's views, is available; additional research examining maternity care provider and system experiences implementing practice changes to increase confidence prior to labor and birth in all settings is needed. These research recommendations are consistent with multistakeholder research priorities identified after a series in The Lancet on midwifery; they include identifying and describing aspects of care that optimize physiologic processes for healthy childbearing women and newborns and assessing women's views and preferences across settings about maternal and newborn care . Development of a prenatal care model intentionally focused on supporting the normalcy of pregnancy and birth, helping women feel confident for physiologic birth, and reducing unnecessary interventions, and examining the effect of such a model on care outcomes, women's satisfaction, and cost of care is necessary.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Information about maternity care providers’ perspectives regarding prenatal preparation for physiologic birth, similar to women's views, is available; additional research examining maternity care provider and system experiences implementing practice changes to increase confidence prior to labor and birth in all settings is needed. These research recommendations are consistent with multistakeholder research priorities identified after a series in The Lancet on midwifery; they include identifying and describing aspects of care that optimize physiologic processes for healthy childbearing women and newborns and assessing women's views and preferences across settings about maternal and newborn care . Development of a prenatal care model intentionally focused on supporting the normalcy of pregnancy and birth, helping women feel confident for physiologic birth, and reducing unnecessary interventions, and examining the effect of such a model on care outcomes, women's satisfaction, and cost of care is necessary.…”
Section: Discussionmentioning
confidence: 80%
“…These research recommendations are consistent with multistakeholder research priorities identified after a series in The Lancet on midwifery; they include identifying and describing aspects of care that optimize physiologic processes for healthy childbearing women and newborns and assessing women's views and preferences across settings about maternal and newborn care. 33 Development of a prenatal care model intentionally focused on supporting the normalcy of pregnancy and birth, helping women feel confident for physiologic birth, and reducing unnecessary interventions, and examining the effect of such a model on care outcomes, women's satisfaction, and cost of care is necessary. In addition, development of a clinically useful tool to measure women's confidence for physiologic birth prenatally may help maternity care providers guide and individualize care.…”
Section: Implications For Clinical Practice Research and Policymentioning
confidence: 99%
“…The Lancet Global Health published a global identification of future research priorities to improve maternal and newborn health outcomes. 5 It demands that we ask different questions to address complex and systemic challenges in pregnancy and childbirth care; access to midwifery care in the United States is one of those challenges. The Patient Protection and Affordable Care Act increased financial access to health care for all US citizens, including requiring maternity care as an essential health benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up study identified top research priorities to improve maternal and newborn health. The second top priority was to “evaluate the effectiveness of midwife‐led care when compared to other models of care across various settings, particularly on rates of fetal and infant death, preterm birth, and low birthweight.” (p e777)…”
Section: Introductionmentioning
confidence: 99%
“…1,12 Much less research exists on enhancing the respectful, supportive, women-and newborn-centered, high-quality care for all that prevents complications and enables timely response when they arise. Most research has focused on obstetric areas of interest: the clinical and emergency interventions needed when complications arise.…”
Section: The Evidencementioning
confidence: 99%